EKSISTENSI DAN TRANSFORMASI BUDAYA LOKAL DALAM STRATEGI KETAHANAN EKONOMI DI KOTA PADANG SUMATERA BARAT - Kadariah, Siti; Syahrizal, Rodi; Sari, Sri Dinda Nila (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
The research aims to find out the government's efforts in maintaining the existence and transformation of local culture in the Economic Resilience Strategy in Padang City, West Sumatra, the OVOP approach uses a qualitative method that is analyzed with NVivo 12, The results of this research are The results of data management show that problems in the development of SMEs in Padang City can be influenced by several things such as market segmentation, consumer behavior, regulatory enforcement, SME funding, cultural existence and SME product branding. The grouping of the problems is based on the findings in the study, of the problems. The existence of culture is the main problem in the development of SMEs in Padang City, based on the answers of respondents with different percentages of the Cooperative and SME Office at 22.22%, the Trade Office at 16.67%, DPMPTSP at 0%, and Customary Institutions at 57.14%. Enforcement of regulations by the Cooperativeand SME Office is 33.33%, the Trade Office is 8.33%, DPMPTSP is 0%, and Glue.